Pemanfaatan Media Audio Visual dalam Mengembangkan Motivasi Belajar Siswa pada Pembelajaran IPS Kelas X IIS MAS Islamic Centre Medan - Amini Amini; Anissa Siregar; Halimatussa’diyah Br Tanjung; Ika Siti Wulandari; Indah Anisyah Dianti; Novia Armaya Sipahutar (Departement of Mathematics Education, 2023)
This research was motivated by the researcher’s curiosity about the use of audio-visual media used in social studies learning at the MAS Islamic Center. Audio-visual media is a medium that displays images with sound so that learning to use this media becomes more interesting. A number of tools used by teachers in conveying concepts, ideas and experiences captured by the senses of sight and hearing based on the understandings that have been given. The use of audio-visual learning media is based on the problem of low student learning motivation in the learning process which causes students to be less active in paying attention to lessons. This research uses a qualitative approach with a descriptive type of research. Using a descriptive type of research, namely because it wants to describe the use carried out by increasing learning motivation in social studies learning at the MAS Islamic Center. Data obtained by observation and interview data collection techniques.